Production of submicron Al₂O₃ powders by electrochemical dissolution of aluminum in the presence of nitric acid - Balabanov, S.S.; Drobotenko, V.V.; Permin, D.A.; Rostokina, E.Ye.; Boldin, M.S.; Murashev, A.A. (Functional Materials, 2018)
A cost-effective and easily scalable method for the synthesis of ultrapure submicron alumina powders with a narrow particle size distribution and high sinterability is proposed. Aqueous solutions of aluminum hydroxide nanoclusters obtained by AC electrochemical dissolution of aluminum metal in the presence of nitric acid were used as a precursor. Hot pressing and vacuum sintering were used to evaluate the possibility of obtaining Al₂O₃ optical ceramics from synthesized powders.